A new approach to attenuate low velocity impact damages on CFRP structures - Amorim, Luís Manuel Machado (2020)
Carbon Fibre Reinforced Polymers (CFRP) have been widely used in advanced markets, such as, the aeronautic, aerospace and military ones. Despite their extraordinary mechanical properties and low density, advanced composites, due to their intrinsic brittleness and layer-by-layer nature, present some vulnerability when submitted to impact, dynamic and flexural loading. Low velocity impacts (LVI) are one of the most dangerous events that composite laminate can face in their life time. These solicitations may develop imperceptible internal laminate damages, namely delaminations, that tend of propagate in service, compromising part performance. In order to improve interlaminar crack propagation, some works were already carried out using interleaved thin veils between laminate layers to enhance the interlaminar Mode I and II fracture toughness. In this work, a study was carried out on the distribution of stresses across the thickness of a carbon/epoxide laminate typically used in structural aircraft components, to define between which specific layers would be better to interleave thin veils made from four different materials (glass, carbon, aramid and polyester) to achieve better LVI damage tolerance. Samples made from the selected structural carbon/epoxy laminate were then produced by vacuum bag infusion with those thin veils located between their most appropriated layers to be submitted experimental testing and compare their mechanical and LVI performances with those without using interleaved veils. All studied laminates were observed under scanning electron microscopes (SEM) for assessing their processing quality and submitted to interlaminar shear strength (ILSS) and LVI tests to evaluate their delamination resistance and impact response, respectively.